ANALISIS HUBUNGAN PENILAIAN INFRASTRUKTUR DESA BERDASARKAN INDEKS DESA MEMBANGUN (IDM) DESA METODE SINTAX CONTRAST HELMERT DI KABUPATEN WONOGIRI - iwan ristanto, Iwan Ristanto; Handiana Devi, Rida; Azhar Firdausi, Annisa (Inisiasi, 2024)
Wonogiri Regency, there are 299 villages with village status that receive Village Fund (DD) allocations from the Central Government. Based on the Village Development Index (IDM), the average status of villages in Wonogiri Regency is as underdeveloped villages and developing villages. One of the reservoirs of poverty in Wonogiri Regency is in Kismantoro District and Tirtomoyo District. Limited human resources, in this case the Activity Implementation Team (TPK) in the field of village development, are an obstacle constraint in village development in Tirtomoyo District, Wonogiri Regency. This research aims to provide a public test in an assessment of the implementation of village infrastructure development in Tirtomoyo sub-district based on the status of the Village Development Index (IDM). The assessment analysis uses the Helmert contrast syntax statistical method with two types of variables, namely the independent variable (IDM status) and the dependent variable. dependent variable (making RAB and making concrete quality). In carrying out activities to make RAB and concrete quality mixtures, pre-test and post-test assessments are carried out. The results of the assessment using the Helmert Pos Hoc contrast test with the help of SPSS software show that H0 is rejected, meaning; The IDM status of independent villages is influential there is a difference compared to the IDM of developed villages, and is developing in the implementation of activities for making RAB and quality concrete mixes. Whereas H0 is accepted meaning; IDM status in developed villages has no effect/there is no difference compared to IDM in developing villages in terms of the ability to make RAB and concrete mix quality.